Outdoor Time, Screen Time, and Connection to Nature: Troubling Trends Among Rural Youth?. Issue 8 (October 2019) - Larson, Lincoln R.; Szczytko, Rachel; Bowers, Edmond P.; Stephens, Lauren E.; Stevenson, Kathryn T.; Floyd, Myron F.
Evidence suggests that contemporary children are spending less time outdoors than their predecessors. Concurrent reports also highlight the rise of electronic media use in the lives of youth. We explored relationships between self-reported outdoor time, screen time, and connection to nature in a sample of sixth- to eighth-grade students across rural South Carolina ( N = 543). We found that most youth spent time outdoors, but they spent more time with electronic media. The outdoor versus screen time discrepancy was particularly pronounced for girls, African Americans, and eighth graders. Connection to nature, linked to outdoor time, was highest among boys, White students, and sixth graders. Our study contributes to growing evidence highlighting the negative influence of escalating screen time on outdoor time and connection to nature during adolescence. Programs designed to address these troubling trends could focus on two groups at particularly high risk: girls and youth of color.